1.37 Å Crystal structure of pathogenic factor pectate lyase from Acidovorax citrulli. Issue 8 (5th June 2013) - Tang, Qun; Liu, Yan‐Ping; Ren, Zheng‐Guang; Yan, Xiao‐Xue; Zhang, Li‐Qun
ABSTRACT: Pectates lyase (Pel) plays an important role in bacteria pathogenicity. The crystal structure of Pel from Acidovorax citrulli (AcPel) has been solved to 1.37 Å resolution. AcPel belongs to the polysaccharide lyase family 1 (PL1), which has a characteristic right‐handed β‐helix fold. AcPel is similar with other Pels in the PL1 family, but also shows some differences at the substrate binding site. Proteins 2013; 81:1485–1490. © 2013 Wiley Periodicals, Inc.